Devil's chew toy : a novel - Osler, Rob (Crooked Lane, 2022)
"Seattle teacher and part-time blogger Hayden McCall wakes sporting one hell of a shiner, with the police knocking at his door. It seems that his new crush, dancer Camilo Rodriguez, has gone missing and they suspect foul play. Determined to find answers, pint-sized, good-hearted Hayden seeks out two of Camilo's friends--Hollister and Burley--both lesbians and both fiercely devoted to their friend. From them, Hayden learns that Camilo is a 'Dreamer' whose parents had been deported years earlier, and whose sister, Daniela, is presumed to have returned to Venezuela with them. Convinced that the cops won't take a brown boy's disappearance seriously, the girls join Hayden's hunt for Camilo. The first clues turn up at Barkingham Palace, a pet store where Camilo had taken a part-time job. The store's owner, Della Rupert, claims ignorance, but Hayden knows something is up. And then there's Camilo's ex-boyfriend, Ryan, who's suddenly grown inexplicably wealthy. When Hayden and Hollister follow Ryan to a secure airport warehouse, they make a shocking connection between him and Della--and uncover the twisted scheme that's made both of them rich. The trail of clues leads them to the grounds of a magnificent estate on an island in Puget Sound, where they'll finally learn the truth about Camilo's disappearance--and the fate of his family"